2002
DOI: 10.1079/ber2002153
|View full text |Cite
|
Sign up to set email alerts
|

Temperature and food quality effects on growth, consumption and post-ingestive utilization ef.ciencies of the forest tent caterpillar Malacosoma disstria (Lepidoptera: Lasiocampidae)

Abstract: Temperature and food quality can both influence growth rates, consumption rates, utilization efficiencies and developmental time of herbivorous insects. Gravimetric analyses were conducted during two consecutive years to assess the effects of temperature and food quality on fourth instar larvae of the forest tent caterpillar Malacosoma disstria Hübner. Larvae were reared in the laboratory at three different temperatures (18, 24 and 30 degrees C) and on two types of diet; leaves of sugar maple trees Acer saccha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
77
1
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 47 publications
11
77
1
6
Order By: Relevance
“…Another factor that has probably interfered with the development of this stage was their non adequacy to the laboratorial conditions for, as it is a species with a very long cycle, its development may be influenced by seasonal climatic variations, as observed from Tolype ventriosa Draudt, 1927 (Lepidoptera; Lasiocampidae) (Specht et al, 2004). With regards to environmental factors, Levesque et al (2002), found evidence of the influence of temperature and luminosity on the larvae development of another lasiocampid, while Daly (1985) showed an influence of the breeding regimens on the growth rates and on morphometry in populations as well as among individuals from the same population.…”
Section: Resultsmentioning
confidence: 99%
“…Another factor that has probably interfered with the development of this stage was their non adequacy to the laboratorial conditions for, as it is a species with a very long cycle, its development may be influenced by seasonal climatic variations, as observed from Tolype ventriosa Draudt, 1927 (Lepidoptera; Lasiocampidae) (Specht et al, 2004). With regards to environmental factors, Levesque et al (2002), found evidence of the influence of temperature and luminosity on the larvae development of another lasiocampid, while Daly (1985) showed an influence of the breeding regimens on the growth rates and on morphometry in populations as well as among individuals from the same population.…”
Section: Resultsmentioning
confidence: 99%
“…Taking into account the greater toughness of Salix viminalis leaves, the level of mechanical defence of Spiraea tomentosa leaves is obviously not sufficiently effective to defend against E. clorana because this species can also tolerate it. The leaves of Spiraea tomentosa offer larval E. clorana phagostimulants, like sugars (Harborne 1993;Levesque et al 2002), the concentrations of which are greater in Spiraea tomentosa leaves than in those of Salix viminalis. Their higher levels usually result in a shorter duration of larval development and pupal period, as well as greater body mass (Hwang and Lindroth 1997;Kaitaniemi et al 1998;Łukowski et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Because larger trees have greater proportions of their canopy exposed to direct sunlight and because light-exposed leaves are the preferred food of FTC (Levesque et al, 2002), larger trees may have suffered proportionally greater defoliation than smaller trees. Hence, larger trees would have been most negatively affected by FTC, whereas the most suppressed trees, for which light availability (GLI) increased by 23-40% without, would have benefited the most from increased light levels from tree removal.…”
Section: Discussionmentioning
confidence: 99%
“…Species-specific canopy openness parameters determine the degree of light extinction by neighbours but these parameters are estimated from trees with no signs of disease or senescence (Lefranç ois et al, 2008). In reality, both FTC and selection logging would alter light availability for individual trees by introducing intra-specific variation in crown openness from selective feeding behaviour of FTC (Levesque et al, 2002) and, respectively, by intra-and interspecific variation of crown extension growth rates following disturbance (Runkle and Yetter, 1987).…”
Section: Discussionmentioning
confidence: 99%